Clusterization of banking system of Ukraine and it's optimal criteria - Дорошенко, Александр Григорьевич; Ярмак, Ольга Витальевна (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2017)
The article summarizes the current state of the Ukrainian banking system and on this basis actualized the need for improving effectiveness of banking supervision. In accordance with changes in the basic approach to banking supervision – dividing banks into groups by the size of assets and clustering of banks – the basic criteria of this division have been analyzed in accordance with international practice and the recommendations on the weighted selection criteria for clustering. Taking a cluster approach in implementing banking supervision allows: to optimize the load on the supervisory staff in the control; identify the most important areas for the analysis of the bank’s operations; coordinate the activity of the supervisory bodies, financial monitoring and currency control. In most countries monitoring bodies use the officially recognized bank rating system CAMELS. This system is used by the NBU to determine and the bank’s rating based on comprehensive inspection. It enables to determine the overall status of all activities of the bank on the basis of the six components assessment: capital adequacy, the quality of assets, management efficiency and dynamics of income, liquidity and sensitivity to risks. It is also possible to cluster the banking system by the origin and quality of capital assets.This study allows concluding that the NBU having failed to clearly describe the criteria for clustering complicates the understanding of such a procedure and gives grounds for non-transparent decision-making and subjective evaluation of the bank’s activities. The criteria for dividing banks into clusters developed by the National Bank of Ukraine are not regulatory adjusted and non-transparent, which enhances additional risks for banks and destabilizes financial markets.